THE ROLE OF INTERNATIONAL GOVERNANCE IN THE DEMOCRATIZATION OF POSTCONFLICT SOCIETIES THROUGH PROMOTING POLITICAL CULTURE. CASE STUDY: KOSOVO UNDER UNMIK ADMINISTRATION - Bashota, Bardhok; Podrimqaku, Bekim; Bytyqi, Kujtim (European Scientific Journal, ESJ, 2014)
The following study focuses and aims at analyzing one of the latest practices in UN peacekeeping philosophy about the ever increasing role of its administered territories in exercising broader governance authority typical to the ones of a modern state. In this regard, the practice of administering Kosovo by UNMIK has been analyzed as a case study where this mission has been evaluated as a prime example of exercise of this authority. Initially, the study focuses on the analyses of exercise of these powers where UNMIK has fully exercised governmental powers governing Kosovo’s society during the post-war emergency period in particular. Then, apart from governance powers, UNMIK’s scope of activity has been analyzed in a longer-term plan. UNMIK has apparently been perceived as a mission with a state-building mandate even though this has not been stated on the framework of its political objectives. It shall also be explained how the statebuilding function of this mission has been accomplished along with its governance function and therefore it resulted in the establishment and functioning of state capacities for self-governance, with an emphasis on the establishment of institutionalization and democratization components. It shall be further explained that besides establishment of these two interrelated components, UNMIK has played a very active role even when it comes to determining the nature of an electoral system through which efforts have been made to determine the type and level of the political culture in Kosovo. Furthermore, in order to better understand the role that UNMIK has played in Kosovo regarding determining and directing the political culture in Kosovo’s society though designating an electoral system, the study focuses on finding the goals claimed by UNMIK.